Identidades sociales y categorías raciales en la era de la esclavitud y la emancipación. El caso de Manuel Macedonio Barbarín (Buenos Aires, 1792-1836) - Guzmán, Florencia (Anuario de Historia de América Latina, 2020)
In this article, the former slave Manuel Macedonio Barbarín will be used as a central theme in order to explore the social identities and racial categories reflected in the distinct spheres of the social experience of Africans and their descendants, enslaved and free, in the city of Buenos Aires during the final decades of the 18th century and the early 19th century. Through the reconstruction of small trajectories of individualization and collective actions I plan to investigate the complexities that social identities and racial categories assume from their different articulations and in their own historicity, that is to say in their specific contexts of temporality and specialty. The objective of this article is not to draw a biographical outline of the life of Manuel Barbarín, but to use his biography as an example in order to show the way in which urban experiences of slavery, emancipation, integration, otherness and social promotion were noted in the era of slavery and emancipation.